USING MICRO-GESTURES AND BODY MOVEMENT TO TRIGGER ORAL SPEECH IN YOUNG LEARNERS - Abdulloyeva Fotima (Modern American Journals, 2025)
This study investigates the role of micro-gestures and body movement in triggering oral speech production among young learners. The research explores how non-verbal cues such as hand gestures, facial expressions, body posture, and subtle physical movements influence learners’ willingness and ability to speak. Quantitative findings indicate that the systematic use of micro-gestures by teachers significantly increases learners’ oral participation and response frequency. Qualitative results reveal that embodied support reduces speaking anxiety, builds learner confidence, and encourages participation among typically silent students. The findings suggest that movement-based, multimodal teaching approaches play a crucial role in fostering oral communication skills in young learners and should be integrated into early language pedagogy.
Keywords: Oral speech, micro-gestures, body movement, young learners, speaking activation, non-verbal communication